Pengaruh Persepsi Kemudahan, Kepercayaan, Efektivitas, Dan Fitur Penggunaan Terhadap Minat Menggunakan Financial Technologi (Fintech) Pada Aplikasi Shopeepay - Rosita, Ida; Prabowo, Heri; Indiworo, Hawik Ervina; Sutrisno, Sutrisno (Lembaga Pengembangan Kinerja Dosen, 2024)
There are various e-commerce sites, one of which is Shopee, which utilizes financial technology or what is known as financial technology (Fintech) in the form of Shopeepay. Many factors can influence interest in using fintech including perceived ease, trust, effectiveness and features of use. This study aims to determine the effect of perceptions of convenience, trust, effectiveness and usage features on interest in using Shopeepay fintech. This research method is descriptive quantitative, the population in this study are regular UPGRIS management students class of 2018 and class of 2019 who are willing to fill out a research questionnaire with a total of 100 respondents, the sampling technique used is accidental sampling. Data collection was carried out through a questionnaire. Data analysis was carried out through validity and reliability tests, multiple regression analysis and hypothesis testing. Based on the data analysis conducted, it was found that perceived convenience has a positive and significant influence on the intention to use Fintech Shopeepay with a significant value of 0.001, trust has a positive and significant influence on the intention to use Fintech Shopeepay with a significant value of 0.048, effectiveness has a positive and significant influence on the intention to use fintech Shopeepay with a significant value of 0.000, features of use have a positive and significant influence on interest in using fintech Shopeepay with a significant value of 0.043. This means that the influence of perceptions of convenience, trust, effectiveness and features of use has an effect on interest in using Shopeepay fintech.